PENGARUH JENIS SUSU TERHADAP SINERESIS, WATER HOLDING CAPACITY, DAN VISKOSITAS YOGURT - Setyawardani, Erika; Rahardjo, Agustinus Hantoro Djoko; Setyawardani, Triana (ANGON: Journal of Animal Science and Technology, 2021)
Background. The aim of the study was to determine the effect of different types of milk on syneresis, WHC, and yogurt viscosity. Materials and methods. The research material used include 3 l of pasteurized fresh cow's milk, 3 l of pasteurized fresh goat's milk, 2 l of commercial cow's milk (low fat), 2 l of commercial cow's milk (full fat), 13.5 g commercial yogurt starter and 2.5 g collagen. The research design used was a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments in this study were (P1) fresh pasteurized cow's milk, (P2) fresh pasteurized goat's milk, (P3) commercial cow's milk low fat, (P4) commercial cow's milk full fat, (P5) combination cow's milk and goat's milk. Results. The results of the analysis of variance showed that there was a significant effect (P<0.01) on the value of syneresis, WHC, and viscosity of yogurt. The average of syneresis was 23,75 ± 10,76 % , WHC was 55.02 ± 17.68 %, and viscosity was 841.2 ± 360.7 cP. Conclusion. Yogurt made with full fat commercial milk has high viscosity and WHC but the syneresis value is low.